Brief Summary of Holochlorini (Orthoptera: Tettigoniidae: Phaneropterinae), with Description of Seven New Species from China - Liu, Chun-Xiang (Zootaxa, 2011)
Inclusion of the tribe Holochlorini has been questionable, for its complicated history and its controversial important diagnostic character about structure of tibial tympana. Here we briefly introduce its history and summarize its inclusion in the world and in China. We also introduce a newly recorded genus from China, Arnobia, and other two genera in the tribe, Psyrana and Phaulula, provide a list of Chinese species for the three genera, separately, together with the key to species of the three genera. At the same time, we describe seven new species to science in the Holochlorini, i.e., Arnobia hainanensis sp. nov., Arnobia guangxiensis sp. nov., Phaulula apicalis sp. nov., Psyrana magna sp. nov., Psyrana heptagona sp. nov., Parapsyra brevicauda sp. nov., and Sinochlora semicircula sp. nov. Diagnostic illustrations are presented.